Pagetoid Reticulosis Woringer–Kolopp type, a Rare Variant of Mycosis Fungoides - Roque Ferreira, Barbara (2016)
Introduction: Pagetoid reticulosis is a rare variant of mycosis fungoides. The typical lesion is a solitary, slow-growing, well circumscribed and hyperkeratotic plaque or patch. A widespread form was also described, but, according to the last classification, the term is reserved for the localized variant (classically, "Woringer-Kolopp").Case report: We observed a 58-year-old patient, with a solitary keratotic plaque, 15mm x 18mm, on the plantar surface of the left halux. The lesion had been present for years, recently with local pain. The biopsy showed an infiltrate of small atypical lymphocytes with pagetoid invasion of the epidermis. On immunohistochemistry, a predominance of CD4+ T cells was observed. The results confirmed the diagnosis of pagetoid reticulosis. Two months after 0.05% clobetasol propionate applied daily, significant improvement was observed.Conclusions: Although pagetoid reticulosis is considered a variant of mycosis fungoides, it shows characteristic clinical and histopathological features, and a heterogenous immunophenotype. Extracutaneous involvement has not been reported.